Differences in outcomes of oesophageal and gastric cancer surgery across Europe1. Issue 1 (23rd November 2012) - Dikken, J. L.; van Sandick, J. W.; Allum, W. H.; Johansson, J.; Jensen, L. S.; Putter, H.; Coupland, V. H.; Wouters, M. W. J. M.; Lemmens, V. E. P.; van de Velde, C. J. H.
Abstract Background: In several European countries, centralization of oesophagogastric cancer surgery has been realized and clinical audits initiated. The present study was designed to evaluate differences in resection rates, outcomes and annual hospital volumes between these countries, and to analyse the relationship between hospital volume and outcomes. Methods: National data were obtained from cancer registries or clinical audits in the Netherlands, Sweden, Denmark and England. Differences in outcomes were analysed between countries and between hospital volume categories, adjusting for available case‐mix factors. Results: Between 2004 and 2009, 10 854 oesophagectomies and 9010 gastrectomies were registered. Resection rates in England were 18·2 and 21·6 per cent for oesophageal and gastric cancer respectively, compared with 28·5–29·9 and 41·4–41·9 per cent in the Netherlands and Denmark (P < 0·001). The adjusted 30‐day mortality rate after oesophagectomy was lowest in Sweden (1·9 per cent). After gastrectomy, the adjusted 30‐day mortality rate was significantly higher in the Netherlands (6·9 per cent) than in Sweden (3·5 per cent; P = 0·017) and Denmark (4·3 per cent; P = 0·029). Increasing hospital volume was associated with a lower 30‐day mortality rate after oesophagectomy (odds ratio 0·55 (95 per cent confidence interval 0·42 to 0·72) for at least 41 versus 1–10 procedures per year) and gastrectomy (odds ratio 0·64 (0·41 to 0·99) for at least 21 versus 1–10 procedures per year). Conclusion: Hospitals performing larger numbers of oesophagogastric cancer resections had a lower 30‐day mortality rate. Differences in outcomes between several European countries could not be explained by differences in hospital volumes. To understand these differences in outcomes and resection rates, with reliable case‐mix adjustments, a uniform European upper gastrointestinal cancer audit with recording of standardized data is warranted. Copyright © 2012 British Journal of Surgery Society Ltd. Published by John Wiley & Sons, Ltd.